A COMPARATIVE STUDY BETWEEN ENGLISH AND INDONESIAN ADDRESS SYSTEM USED IN NOVEL ENTITLED TWILIGHT SAGA AND LASKAR PELANGI TETRALOGY - PRATIWI , MUSTAFIAH NUR (2010)
This study investigates the comparation of English and Indonesian address system in novel entitled Twilight Saga and Laskar Pelangi Tetralogy. The objectives of this study are to clarify the variations of address system and compare them, and to find out the reasons of using address system and compare them. This is a descriptive qualitative research which takes a document oriented as the method of collecting data. By this method, the writer uses the novel entitled Twilight Saga and Laskar Pelangi Tetralogy as the data source, and the data taken are English and Indonesian address system. As the comparison, there are the data of English address system and Indonesian address system. The results of the research show that firstly, the types of the variations of address system come into 13 types; first name, last name, nick name, full name, intimate name, kinship name, mockery, title, profession, title plus first name, title plus last name, title plus full name and title plus profession. Secondly, there are 9 reason in using address system; showing anger, showing anxiety, showing intimacy, showing kinship, showing mockeries, showing name, showing power or authority, showing respectful, and showing solidarity. Lastly, the comparative of English and Indonesian address system. The similarity is there are some types of address system that used in English and Indonesian address system. The difference is there is type of address system that did not used in Indonesian address system.